Testing nano-silver food packaging to evaluate silver migration and food spoilage bacteria on chicken meat. Issue 6 (2nd June 2016) - Gallocchio, Federica; Cibin, Veronica; Biancotto, Giancarlo; Roccato, Anna; Muzzolon, Orietta; Carmen, Losasso; Simone, Belluco; Manodori, Laura; Fabrizi, Alberto; Patuzzi, Ilaria; Ricci, Antonia
ABSTRACT: Migration of nanomaterials from food containers into food is a matter of concern because of the potential risk for exposed consumers. The aims of this study were to evaluate silver migration from a commercially available food packaging containing silver nanoparticles into a real food matrix (chicken meat) under plausible domestic storage conditions and to test the contribution of such packaging to limit food spoilage bacteria proliferation. Chemical analysis revealed the absence of silver in chicken meatballs under the experimental conditions in compliance with current European Union legislation, which establishes a maximum level of 0.010 mg kg –1 for the migration of non-authorised substances through a functional barrier (Commission Regulation (EU) No. 10/2011). On the other hand, microbiological tests (total microbial count, Pseudomonas spp. and Enterobacteriaceae) showed no relevant difference in the tested bacteria levels between meatballs stored in silver-nanoparticle plastic bags or control bags. This study shows the importance of testing food packaging not only to verify potential silver migration as an indicator of potential nanoparticle migration, but also to evaluate the benefits in terms of food preservation so as to avoid unjustified usage of silver nanoparticles and possible negative impacts on the environment.